Development of self-acceptance competence in the process of studying the course "Human resource management" (Journal of Educational Sciences, 2024)
The article presents the results of research and integration into the educational program of the Master of Business Administration (MBA) of the competence of self-acceptance, which is currently in the circle of attention of employers, entrepreneurs and managers of different levels and areas of business.  The relevance and significance of this study are due to the fact that, despite the surge of interest, self-acceptance is not clearly defined as a competence that has a specific content, value, dynamics and technology of mastering in the higher professional educational process. The author of the article presents the experience of defining this competence and research in action (Achene Research) of enriching the content of the educational program "Human Resource Management" in MBA with relevant information and technological development strategies. The research was carried out with the use of observation methods, analysis of theoretical sources and publications of practicing psychologists-consultants, study of master's students' activity products, self-assessment of master's students, expert evaluation.  Undergraduates of the Kazakh-British Technical University took part in the practical part of the study. The result of the study was the clarification of the concept of "self-recognition" in terms of the competence approach to the content of MBA education; determination of the issues of the content and technology of self-recognition that are relevant for MBAs; identification of the types of attitude of MBAs to the activity of self-recognition; identification of training situations that develop the competence of self-recognition of MBAs. The results of the presented research are a contribution to the methodology and technology of integrating self-acceptance competence into the content of MBA educational programs.Keywords: recognition, self-acceptance, interpersonal interaction, business relationships, productive work environment, psychology of business relationships, coaching approach in education, effective communication, Master of Business Administration.